(untitled) (OODBODHAN, 2025)
Landslides in Phewa Lake Catchment, triggered by slope failure, poses risks to life, infrastructure, and degradation of soil quality while contributing to shrinkage of Phewa Lake. This study identifies potentially unstable slope within the catchment using landslide susceptibility mapping and then assesses slope stability of a selected unstable slope. A landslide susceptibility map (LSM) is developed using Geographic Information Systems (GIS) considering key factors such as slope, aspect, curvature, stream proximity, proximity to faults, proximity to thrust, rock/soil types and rainfall patterns applying the Frequency Ratio (FR) method. The prediction ratio obtained from FR shows the slope as the principal influencing factor for landslide occurrence followed by rainfall pattern and then rock/soil types. The LSM with 73.49% accuracy evaluated from Area under curve, indicates good performance of the model considered, classifies the catchment area into five susceptibility classes: very low (18.05%), low (29.92%), moderate (27.50%), high (13.19%) and very high (11.33%). The areas with high and very high susceptibility indicates higher possibility of slope failure emphasizing the priority for slope stability analysis during land-use planning and preparation of disaster mitigation strategy. Slope stability analysis will be conducted on selected unstable slope. Samples were collected from the selected slope, and direct shear tests were conducted to determine shear strength parameters. The next phase of the research involves a detailed slope stability analysis using Finite Element Analysis (FEA) in Plaxis 2D, applying the Shear Strength Reduction (SSR) method to estimate the Factor of Safety (FoS).